Plasma Exosomes Transfer miR-885-3p Targeting the AKT/NFκB Signaling Pathway to Improve the Sensitivity of Intravenous Glucocorticoid Therapy Against Graves Ophthalmopathy - Sun, Jingxue; Wei, Jiaxing; Zhang, Yaguang; Li, Jingjing; Li, Jian; Yan, Jiazhuo; Guo, Min; Han, Jun; Qiao, Hong (Frontiers in Immunology, 2022)
Graves ophthalmopathy (GO), a manifestation of Graves’ disease, is an organ-specific autoimmune disease. Intravenous glucocorticoid therapy (ivGCs) is the first-line treatment for moderate-to-severe and active GO. However, ivGCs is only effective in 70%–80% of GO patients. Insensitive patients who choose 12-week ivGCs not only were delayed in treatment but also took the risk of adverse reactions of glucocorticoids. At present, there is still a lack of effective indicators to predict the therapeutic effect of ivGCs. Therefore, the purpose of this study is to find biomarkers that can determine the sensitivity of ivGCs before the formulation of treatment, and to clarify the mechanism of its regulation of ivGCs sensitivity. This study first characterized the miRNA profiles of plasma exosomes by miRNA sequencing to identify miRNAs differentially expressed between GO patients with significant improvement (SI) and non-significant improvement (NSI) after ivGCs treatment. Subsequently, we analyzed the function of the predicted target genes of differential miRNAs. According to the function of the target genes, we screened 10 differentially expressed miRNAs. An expanded cohort verification showed that compared with NSI patients, mir-885-3p was upregulated and mir-4474-3p and mir-615-3p were downregulated in the exosomes of SI patients. Based on statistical difference and miRNA function, mir-885-3p was selected for follow-up study. The in vitro functional analysis of exosomes mir-885-3p showed that exosomes from SI patients (SI-exo) could transfer mir-885-3p to orbital fibroblasts (OFs), upregulate the GRE luciferase reporter gene plasmid activity and the level of glucocorticoid receptor (GR), downregulate the level of inflammatory factors, and improve the glucocorticoid sensitivity of OFs. Moreover, these effects can be inhibited by the corresponding miR inhibitor. In addition, we found that high levels of mir-885-3p could inhibit the AKT/NFκB signaling pathway, upregulate the GRE plasmid activity and GR level, and downregulate the level of inflammatory factors of OFs. Moreover, the improvement of glucocorticoid sensitivity by mir-885-3p transmitted by SI-exo can also be inhibited by the AKT/NFκB agonist. Finally, through the in vivo experiment of the GO mouse model, we further determined the relationship between exosomes’ mir-885-3p sequence, AKT/NFκB signaling pathway, and glucocorticoid sensitivity. As a conclusion, plasma exosomes deliver mir-885-3p and inhibit the AKT/NFκB signaling pathway to improve the glucocorticoid sensitivity of OFs. Exosome mir-885-3p can be used as a biomarker to determine the sensitivity of ivGCs in GO patients.